Comparative Analysis of the Implementation of Small-Scale Government Cooperation with Business Entities (KPBU): A Comparative Study between Indonesia and South Korea in the Perspective of Efficiency, Regulation, and Sustainability - Kurdi Kurdi; Prita Amalia; Yuki Mahardhito Adhitya Wardhana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Public-Private Partnership (PPP) is a common scheme used in infrastructure development in Indonesia, with the main legal basis in Presidential Regulation Number 38 of 2015 and its derivative regulations, such as Regulation of the Minister of PPN/Head of Bappenas Number 7 of 2023. Although this regulation provides legal certainty, the implementation of Small-Scale PPP still faces obstacles, especially in the clarity of project boundaries, variations in financing methods, and immature evaluation mechanisms. This study aims to analyze the implementation of Small-Scale PPP in Indonesia through a comparative study with South Korea, which has clearer and more flexible regulations and more varied financing options, including the Build-Transfer-Lease (BTL) scheme. Using normative legal methods through a comparative approach, legislation, and conceptual, this study identifies differences in PPP regulations and practices in the two countries to evaluate the effectiveness of the policies implemented. The results of this study are expected to provide recommendations for updating PPP regulations in Indonesia in order to increase legal certainty, regulatory effectiveness, and investment attractiveness in a Small-Scale PPP scheme that is more stable and has more legal certainty